The influence of age categories on performance parameters during on-court testing in wheelchair basketball players - Honnorat, Lorian; Weissland, Thierry; Pradon, Didier; Alberca, Ilona; Rivière, Jean Romain; Brassart, Florian; Vigié, Opale; Faupin, Arnaud (Frontiers in Sports and Active Living, 2025)
IntroductionWheelchair basketball is a highly dynamic sport that requires optimized propulsion techniques, sprint performance, and fatigue resistance. Understanding the biomechanical differences between age groups is crucial for potential estimation and training optimization. This study aimed to analyze the impact of age on sprint performances by comparing junior and senior wheelchair basketball players, while also identifying factors influencing sprint performances beyond age, such as experience, wheelchair characteristics, and classification.Materials and methodsTwenty-two male wheelchair basketball players were divided into two groups: juniors (21 years or younger) and seniors (22 years and older). Participants completed 6 × 20 m repeated sprint tests, during which various biomechanical parameters including propulsion time, cadence, and asymmetry, were measured using inertial measurement units (IMUs). Fatigue indices were calculated by comparing performance across repeated sprints. Principal component analysis and hierarchical clustering were applied to identify key performance differentiators among groups.ResultsJunior players exhibited significantly lower linear wheelchair velocities from the first three pushes, as well as throughout their best sprint compared to seniors, resulting in significantly longer sprint times in junior players. Additionally, the fatigue index was higher for the junior group. However, no significant differences were found in the stabilized velocity phase, maximum velocity, or propulsion asymmetry of the best sprint. Hierarchical clustering analysis revealed three clusters, with experience and wheel size emerging as additional performance differentiators beyond age.ConclusionThe study confirms that age influences, on average, sprint performances in wheelchair basketball, particularly in the initial acceleration phase, but the wide interindividual variabilities within age groups were also linked to experience and wheelchair characteristics.